2020
DOI: 10.1080/13557858.2020.1838456
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a rural Latino community’s perception of the COVID-19 pandemic

Abstract: Objectives: The purpose of our study was to understand the perception of the Latino community in a rural state regarding COVID-19. Over one third of national COVID-19 cases are among Latinos, likely due to an increased prevalence of comorbid risk factors and social determinants of health that make following precautions difficult. Design: Respondents were recruited using snowball sampling as part of a previous effort to establish an academic-community partnership with Latinos in the area. In April 2020, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 33 publications
1
61
1
5
Order By: Relevance
“…Fear of pay cuts, job loss [29], and deportation [30] make migrant workers reluctant to report symptoms [31], making infection detection through screening and treatment a unique challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of pay cuts, job loss [29], and deportation [30] make migrant workers reluctant to report symptoms [31], making infection detection through screening and treatment a unique challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents in the study of perceptions in the rural Latino community suggested, for example, a personalized approach to deliver information, by utilizing email or text messages from nearby universities, their medical providers, or the local health department. 9,21…”
Section: Discussionmentioning
confidence: 99%
“…Authors of a qualitative study in a rural Latino community suggested that risk perceptions and concerns were linked to stress of loss of employment. 21 Responsibility rests with politicians, health authorities, and community leaders to communicate evidence-based information in a manner that is honest and clear, easily accessible, and culturally appropriate. Respondents in the study of perceptions in the rural Latino community suggested, for example, a personalized approach to deliver information, by utilizing email or text messages from nearby universities, their medical providers, or the local health department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of medicinal plants [38] and self-medication are common practices in Peru, especially during the pandemic [20]. However, the fact that people consume one of these measures does not mean that they trust in its e cacy [39] leading them to seek more than one preventive measure such as medicines and to rely on pseudoscienti c beliefs such as the consumption of chlorine dioxide [35]. This practice may result in the population having a false sense of security and relaxing preventive measures against COVID-19 [40].…”
Section: Factors Associated With Chlorine Dioxide Consumptionmentioning
confidence: 99%